Letter from Éamonn Duggan to his fiancée May Kavanagh, written from Brackanraney, Co. Meath - Duggan, Éamonn, 1874-1936; Duggan, May
Duggan's letter may have been written following his release from Lewes prison in mid 1917 when he spent time in Co. Meath. He writes of swimming everyday in the River Boyne and news that Major Charles Heathcote never received his financial claim he sent while he was in Lewes Prison.
Duggan joined the Irish Volunteers on their foundation and fought at the North Dublin Union and later Fr. Mathew Hall during the Easter Rising. He was subsequently imprisoned in Mountjoy, Portland and Lewes prisons, was among those released in the summer of 1917 and successfully stood as a Sinn Féin candidate for South Meath in 1918.
Keywords: Duggan, Éamonn, -- 1874-1936